2020
DOI: 10.3390/rs12193206
|View full text |Cite
|
Sign up to set email alerts
|

Flood Hazard Risk Mapping Using a Pseudo Supervised Random Forest

Abstract: Devastating floods occur regularly around the world. Recently, machine learning models have been used for flood susceptibility mapping. However, even when these algorithms are provided with adequate ground truth training samples, they can fail to predict flood extends reliably. On the other hand, the height above nearest drainage (HAND) model can produce flood prediction maps with limited accuracy. The objective of this research is to produce an accurate and dynamic flood modeling technique to produce flood ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…At regional scale, Burn (1997) has discussed the catchment procedure essential to undertake the flood frequency analysis. Faulkner et al (2016) devised the procedure to estimate the design flood levels using the available station data. Regional hydrological frequency analysis at ungauged sites is also studied by few researchers (Desai and Ouarda, 2021).…”
Section: Stage 2: Regional Regression and Flood Frequency Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…At regional scale, Burn (1997) has discussed the catchment procedure essential to undertake the flood frequency analysis. Faulkner et al (2016) devised the procedure to estimate the design flood levels using the available station data. Regional hydrological frequency analysis at ungauged sites is also studied by few researchers (Desai and Ouarda, 2021).…”
Section: Stage 2: Regional Regression and Flood Frequency Analysismentioning
confidence: 99%
“…To this end, annual maximum discharge values (m 3 s −1 ) were extracted within R (R Core Team, 2019) at hydrometric stations maintained by Environment Canada within the Grand River and Ottawa River watersheds (HY-DAT) (Hutchinson, 2016). Only stations with a period of record >= 10 years of annual maximum discharge (England et al, 2018;Faulkner et al, 2016) were maintained (n = 32 and n = 54, respectively, for the Grand River watershed and the Ottawa River watershed). The minimum, median, and maximum periods of record for the Grand River watershed were 12, 50, and 86 years, respectively.…”
Section: Stage 2: Regional Regression and Flood Frequency Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive urbanization and climate change are more often blamed as the main reasons for such hazards [1,2]. The massive human, economic, and infrastructure losses resulting from flood occurrences necessitate flood management, prediction, and early warning systems [3,4]. At a global scale, in the period 1995-2015, it was reported that 109 million people were influenced by flood hazards, with annual direct costs of 75 billion dollars [5]; only between 2011-2012, indirect damages and losses were reported as 95 billion dollars [6].…”
Section: Introductionmentioning
confidence: 99%
“…Besides traditional methods, machine learning and statistical models have been used to investigate the probability of being flooded [35][36][37][38]. Different topographical, hydrological, and geological condition factors were applied to the existing machine learning models; then, the best conditioning factors and the models with the best results were adopted to generate flood susceptibility maps [35,36]. Moya et al [37] introduced a supervised machine learning classifier to learn from a past event to identify flooded areas during Typhoon Habibis.…”
Section: Introductionmentioning
confidence: 99%